Nitric Oxide and Prostaglandins Potentiate the Liver Regeneration Cascade - Jodi M Schoen Smith; W Wayne Lautt (Canadian Journal of Gastroenterology)
The liver has the remarkable ability to regenerate following damage or surgical resection. Although this feature of the liver has been studied for over 100 years, the trigger of the liver regeneration cascade remains controversial. Recent experimental evidence supports the hypothesis that nitric oxide (NO) and prostaglandins (PGs), released secondary to an increase in the blood flow-to-liver mass ratio following two-thirds partial hepatectomy (PHx), work synergistically to trigger liver regeneration. To extend this research, the hypothesis that NO and PGs are potential therapeutic targets to potentiate the liver regeneration cascade is tested. The NO donor s-nitroso-n-acetylpenicillamine, the phosphodiesterase V antagonist zaprinast (ZAP) and PGI2 each potentiated c-fos messenger RNA expression, an index of initiation of the liver regeneration cascade, following PHx. Also, the triple combination of s-nitroso-n-acetylpenicillamine, ZAP and PGI2 potentiated c-fos messenger RNA expression. These results support the hypothesis that NO and PGs can potentiate initiation of the regeneration cascade. An additional index of liver weight restoration 48 h after PHx was also used to test the hypothesis, because this index encompasses the entire liver regeneration cascade. ZAP and 6-keto-PGF1α, a stable metabolite of PGI2, and the combination of ZAP and 6-keto-PGF1α, each potentiated liver weight restoration 48 h after PHx. These results also provide support for the hypothesis that NO and PGs are possible therapeutic targets to potentiate liver regeneration following surgical resection.